IDENTIFICATION OF RISKS ARISING FROM THE USE OF TRADITIONAL AND ALTERNATIVE JET FUELS: AN ENVIRONMENTAL RISK - Бойченко, С. В.; Хрутьба, В. О.; Яковлєва, А. В.; Антропченко, А. К. (Science-based technologies, 2016)
This work is devoted to the risk analysis of the use of traditional fuels and biofuels in aviation. An important step of risk analysis of the use of biofuels in aviation is the analysis of threats of environmental pollution. Also one of the aspects of the risk analysis is a new trend in research; identification of strengths and weaknesses; that is; the method of SWOT analysis.The analysis of factors influencing the threat of environmental pollution is to identify all sources of threats and assessment of their impact on the environment and humans. The article is identification of risks arising from the use of traditional and alternative fuels for jet aircraft. Discusses stages in the life cycle of fuel usage and the environmental impact of each stage. Also estimated emissions that occur during fuel combustion; thereby becoming relevant to the assessment of environmental risk for population health.